(untitled) (GEON Journal (Management, Organizations and Business), 2017)
Sustainable development has taken special interest in seeking to involve the populations and institutional actors that inhabit and carry out their activities in a territory to generate strategies and action plans that modify problematic situations in opportunities that improve the quality of life of the population. population keeping in balance the environmental base, social relations and economic activities. This is how the research team sought to promote the development and improvement of the quality of life of the population of the municipality of Lejanías - Meta through the construction of a sustainable development model, seeking through the processes of social participation the formulation and implementation of the Territorial Development Plan 2016 - 2019. Likewise, the local capacities of the population were strengthened through the different organisms and mechanisms of citizen participation such as the Community Action Boards, the Territorial Planning Council, the Municipal Council, the associations, other organizations of the solidarity sector and the Council Municipal of Rural Development. Similarly, after formulating the Territorial Development Plan, the population is expected to accompany the municipal administration in the execution, monitoring and evaluation of the same through spaces for citizen participation and the use of ICTs as management tools. that favor citizen oversight and social control.